One example on how colloidal nano- and microparticles could contribute to medicine. (December 2009) - Peteiro-Cartelle, Javier; Rodrííguez-Pedreira, Montserrat; Zhang, Feng; Gil, Pilar Rivera; del Mercato, Loretta L; Parak, Wolfgang J
Nanomedicine, nowadays, is a popular keyword in the media, although everyone seems to associate it with different visions, hopes and even fears. This article gives a perspective from two sides. From the point of view of a materials scientist, it will be pointed out what new materials will be possible, how they will be designed and which properties they could offer for diagnosis and treatment. From the point of view of a medical doctor, it will be pointed out which properties are actually desired and what materials are hoped for practical applications. The two different points of view indicate that, although sophisticated materials with advanced novel properties will be available in the future, they do not automatically match the requirements and demands of clinicians. The discussion is centerd around one example, multifunctional polyelectrolyte capsules, which might act as a ''nanosubmarine'' for in vivo sensing and delivery, which is used to highlight promising interfaces between both disciplines.